2018
DOI: 10.1038/s41419-018-0685-8
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A5 regulates hepatocarcinoma malignancy via CRKI/II-DOCK180-RAC1 integrin and MEK-ERK pathways

Abstract: As a calcium-dependent phospholipid binding annexin protein, annexin A5 (Anxa5) links to the progression, metastasis, survival, and prognosis of a variety of cancers. Current work showed ANXA5 overexpression was positively correlated with the upregulations of CRKI/II and RAC1 in hepatocarcinoma (HCC) patients’ tissues, which potentially enhanced the clinical progression and lymphatic metastasis of HCC. The role and action mechanism of ANXA5 in hepatocarcinoma was then investigated using a hepatocarcinoma Hca-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…Its morbidity and mortality rate are among the highest in the world [1,2]. Tumor metastasis is the major problem leading to its high recurrence with low post-surgical 5-years survival and high mortality [3][4][5]. It is a multistep process, including the invasion of extracellular matrix (ECM), intravasation, translocation, migration and invasion of a secondary site, and finally the formation of metastatic nodules [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Its morbidity and mortality rate are among the highest in the world [1,2]. Tumor metastasis is the major problem leading to its high recurrence with low post-surgical 5-years survival and high mortality [3][4][5]. It is a multistep process, including the invasion of extracellular matrix (ECM), intravasation, translocation, migration and invasion of a secondary site, and finally the formation of metastatic nodules [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Other than S100A4, our study also led us to identify several other potential markers of interest for MM, including annexin A5 [60], as its serum level in patients with colon cancer is related to lymph node metastasis and tumor grades [61], while investigations of its role and action in hepatocarcinoma malignancy has revealed that its knockdown suppressed the expression of key molecules in the integrin and MEK-ERK pathways (mitogen-activated protein kinases-extracellular signal-regulated kinases) [62]. Regarding lamin A/C, Kim et al demonstrated that it forms a perinuclear apical actin cap, resisting nuclear deformation in response to physiological mechanical stresses [63].…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports have shown that ERK and STAT3 pathways are important signal pathways that involved in the development of HCC. 52,53 In addition, c-Myc is an oncogene that participates in the growth of HCC cells. 54 Bcl-xl is found to mediate the survival of HCC cells.…”
Section: Discussionmentioning
confidence: 99%